Mexico 1810-2010. Identity and nation building through secularism (Tzintzun, Revista de Estudios Históricos, 2016)
In this Bicentennial year, to reflect on the process of building the Mexican state is doingon the components of their national identity. In this context, the religious question is,presented as a relevant explanatory factor. In its base, state nationalism found in theecclesiastical institution a major obstacle. Especially because it had established itselfas a community trans-historical, essential, beyond and outside of politics. A pole ofstrength capable of generating membership and provide identity to the social bases.From 1821 to 1917, the transfer of legitimacy from political to religious institutions‘was a complex evolution. The revolutio-nary balance involved the establishmentof a secular model and hence the separation of the religious beliefs of the publicsphere. After the 1992 reform, the adoption of secularism as an essential element ofdemocratic pluralism has led to some reinterpretation of the system, according to therequirements of intemational law. For the Mexican Episcopate, 2010 has served as anoccasion to offer an alternative view of official history. A church-state interactionedges which largely explains the processes of political change in contemporaryMexico.
Keywords: Mexican state; national identity; secularism; society; democracy; Mexican clergy